Gobierno actual de la comunidad indígena de Santa Fe la Laguna - Torres Manríquez, María del Rosario (Universidad Michoacana de San Nicolás de Hidalgo, 2017)
The P’urhépecha people, one of the most powerful before the arrival of the Spaniards, whose territories covered approximately the state of Michoacan, with a political, economic and social development that the Europeans could not des-pise, establishing their residence in the indigenous infrastructure. People who, like others, suffered slavery and the dispossession of the land. In the mid-sixteenth century a part of the Tarascos were refugees by Don Vasco the Quiroga, in the community of Santa Fe de la Laguna, in the year the 1533, a foundation that allowed a mixed and autonomous government, Don Vasco the Quiroga made for this system The Laws and Ordinances inspired by the Utopia of Tomas Moro, Saturnales de Luciano and the primitive Christian. After the death of Quiroga, the town only obeyed orders of the Clergy of Val-ladolid. Town with a long history of litigation for the defense of land that began from its foundation, with Juan Infante. The community passed centuries with legal confrontations for the distri-bution of land, but this town strongly embraced its communal system, also prey, of the land deprivation and invasion by half-bloods and cattlemen of Cocupao, at this stage when the town was sunk in the greatest submission and fear, arises a social fighter named Elpidio Dominguez, at the end of the tenth century, who struggled legally and politically to recover the lands of the population. The community of Santa Fe adapted its system of government to the framework of Mexican legislation, introducing the figures of heads of tenure, with the creation of Municipal Councils, Juvenile Tenure Judges who are cur-rently called Traditional Judges of Tenure and Commissariat of Communal Property and Vigilance Council.

El pueblo P’urhépecha fue uno de los más poderosos antes de la llegada de los españoles, su territorio abarcó aproximadamente lo que es el Estado de Michoacán, contaba con un desarrollo político, económico y social que los europeos no pudieron despreciar sentando su dominio en la infraestructura indígena. Pueblo que al igual que otros su-frió esclavitud y despojo de sus tierras. A mediados del s. XVI una parte de los tarascos fueron reagrupados por Don vasco de Quiroga en la comunidad de Santa Fe de la laguna en 1533, fundación que permitió un gobierno mixto y autónomo, Don Vasco realiza para este sistema las Le-yes y Ordenanzas inspiradas en: la Utopía de Tomas Moro, Saturnales de Luciano y en el cristianismo primitivo. Después de muerto Quiroga el pueblo soló obedeció ór-denes del Clero de Valladolid. Pueblo con una larga trayectoria de litigios por la de-fensa de sus tierras, que comenzó desde su fundación, con el entonces Juan Infante. La comunidad pasó los siglos con golpes legales para el repartimiento de tie-rras, pero esta población abrazó fuertemente su sistema comunal, presa también de despojos e invasiones de tierras por mestizo y ganaderos de Cocupao, en una etapa cuando el pueblo se encontraba hundido en la más grande sumisión y miedo surge en ésta misma un luchador social Elpidio Domínguez a finales del s. XX, quien lidio de manera legal y política para recuperar las tierras de la población. La comunidad de Santa Fe adecuó su sistema de gobierno a lo que marcó la legislación mexicana, introduciendo las figuras de Jefes de Tenencia con la creación de Ayuntamientos, Jueces Menores de Tenencia que actualmente son llamados Jueces Tradicionales de Tenencia y Comisariado de Bienes Comunales y Consejo de Vigilancia.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2017-0373; Humanidades; Gobierno; Ordenanzas; Tierras; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/794